The Impact of Role Conflict on Employee Performance with Work Stress as An Intervening - Sijabat, Rauly; Martanto, Ignatius (Jurnal Economia, 2024)
AbstractBased on empirical phenomenon related to the performance of employees in the Tanjung Emas Semarang Class I Port Authority and Authority office and the theoretical phenomena that show inconsistencies in the findings of the influence between variabelsdirect conductthe research on role conflict, work stress and performance. The influence of role conflict, work stress and performance is outlined in an empirical research model. Data related to the variabels studied were obtained through interviews with 126 employee respondents at Tanjung Emas Class I Port Authority and Harbormaster and Authority Officeand tested by using Structural Equation Modeling (SEM) approach. Statistical test results show that role conflict is statistically proven to have a significant positive effect on work stress; role conflictand work stress are statistically proven to have a significant negative effect on performance. Keywords:Role Conflict, Work Stress, Performance